Enhanced detection of circulating tumor cells using a MUC1 promoter-driven recombinant adenovirus - Wang, Cheng; Gu, Huihui; Cai, Jia; Zhu, Chuandong; Zheng, Qin; Xu, Hanfeng; Wang, Lixue; Wan, Yuan (Frontiers in Oncology, 2025)
IntroductionCirculating tumor cells (CTCs) have attracted significant interest as a biomarker for cancer diagnosis. In this study, we judiciously constructed a recombinant MUC1-dependent adenovirus (rAdF35-MUC1) that can selectively replicate and overexpress copepod super green fluorescent proteins (copGFP) in MUC1-positive tumor cells to investigate its role in the detection of CTCs.MethodsWe conducted a comparative study between rAdF35-MUC1 and the existing hTERT-dependent adenovirus (rAdF35-hTERT). Breast cancer cell lines and healthy human peripheral blood mononuclear cells (PBMCs) were infected with both viral constructs to evaluate infection efficiency and the incidence of false-positive cells. CTC Model Samples were employed to determine detection rates, and clinical samples from breast cancer patients were analyzed to preliminarily evaluate the efficacy of CTC detection in a clinical context.ResultsIn preclinical and clinical studies, rAdF35-MUC1 exhibited a significantly high detection efficiency for breast cancer cells, outperforming the existing hTERT-dependent adenovirus (rAdF35-hTERT), especially in detecting CTCs at low quantities. Moreover, rAdF35-MUC1 demonstrated reduced incidence of false positives in healthy PBMCs compared to rAdF35-hTERT.ConclusionIn brief, rAdF35-MUC1 emerges as a potent tool for the sensitive and specific identification of CTCs derived from breast cancer patients, holding clinical translation potential for advancing cancer (early) diagnosis, treatment monitoring, and prognosis.